Music, theology, and worship selected writings, 1841-1896 - Friedmann, Jonathan L., 1980- (McFarland & Co., 2011)
"This book offers a representative collection of insightful essays about devotional music from nineteenth-century scholars and practitioners. Addressing the social and theological import of church music, this text also explores the divine quality of the human voice, the spiritual efficacy of congregational singing, and a host of topics pertinent to church life"--Provided by publisher.